UMP and AITO Firework collaborate in the field of fire safety - Nor Salwana, Mohammad Idris (2020)
Pekan, 14 July 2020 - Universiti Malaysia Pahang (UMP) and AITO Firework Holding Sdn. Bhd. (AITO) signed a Memorandum of Understanding (MoU) to develop learning management system modules and research partnerships related to the field of fire safety.